Pemberdayaan Kader Melalui Pelaksanaan Bantuan Hidup Dasar (BHD) di Wilayah Pesisir Kabupaten Mamuju - Syafruddin Ali Salaka; Iqra S Iqra S; I Made Sudarta (Jurnal Pengabdian Masyarakat JUPEMANDO, 2026)
Communities living in coastal areas are at higher risk for drowning and cardiac arrest events. Therefore, improving first aid knowledge and skills is essential. This community engagement program aimed to enhance the capacity of community health cadres and coastal residents in performing Basic Life Support (BLS). The methods included socialization, training, demonstration, and evaluation using pre-test and post-test assessments. A total of 80 participants were involved, consisting of health cadres, midwives, village officials, and fishermen. The results showed an increase in knowledge, with 75% categorized as good. Participants were also able to independently perform BLS skills. This program demonstrates the effectiveness of interprofessional collaboration–based training in improving emergency preparedness in coastal communities.